3D Printable Micro/Macro Dual Driving Multipede Millirobot and Its Characterization for Multi-Locomotory Modes - Lu, Qing; Feng, Yue; Song, Ki-Young; Zhang, Wen-Jun (IEEE/ASME transactions on mechatronics, 2023)
Aiming at both high motion precision and high velocity is arduous in the development of miniature robots because of contradictory aspects between the precision and the velocity. In this article, we developed a simple three-dimensional printable micro/macro dual driving multipede millirobot to successfully satisfy both high precision and high velocity, by employing bio-inspired titled legs through the concept of anisotropic friction. Four locomotory modes (stick, stick-slip, pure-slip, and jumping) of the millirobot were carefully examined and effectively manipulated to switch micro and macro motions for high precision and high velocity, respectively. We investigated the effects of external conditions (mobile surface roughness and excitation waveform) and internal conditions (geometric parameters of driving legs) on the locomotory modes. The millirobot achieved a step resolution of 2  μ m in the micromotion and maximum mobile velocity of 800 mm/s in the macromotion. In addition, our millirobot can perform bi-directional motion (forward and backward) with quick return characteristics.